New Straits Times, 25 Jun 2008 - Roziana Hamsawi (The New Straits Times Press (M) Bhd, 2008)
KUWAIT Finance House (Malaysia) Bhd (KFHMB) said it is fully committed to its investments in Malaysia, despite the scaling down of several key projects.